Online Learning Transition Based on Internet and E-Commerce Classroom Learning Management System (LMS) - Sudaryono Sudaryono; Alfiah Khoirunisa; Abdullah Dwi Srenggini (Universitas Raharja, 2021)
In the era of digital information, especially in the field of education, online learning methods are currently developing rapidly in the learning and teaching process. The aim of this project is to provide a uniform and consistent user interface in the new learning management system (LMS) for students and faculties and to promote super users who will assist the faculty in a smooth transition from. The curriculum template is provided in the LMS for online learning processes or called e-Learning and has various training opportunities with super users that are interactive so that online learning will be effective and quality. (57%) report results from faculty feeling competent or very competent (36%) in their ability to use. Canvas ™ LMS after project implementation; There are several survey comments reflecting a positive response to the transition to Canvas ™. This project produces quality, student-centered online learning. Where is in accordance with the standardized template framework.